I have a sequence $a_n$: $1,2, 2^2, 2^{2^2}, 2^{2^{2^2}}, ...$

I would like to know how to factor $b_i = a_i-a_{i-1}$ where $a_0=1$

All I've been able to figure out so far is that 1 + $\sum\limits_{i=1}^nb_i = a_n$, which doesn't seem to go anywhere...

  • Do you mean that $a_n: 1, 2, 2^2, (2^2)^2, ((2^2)^2)^2$ or $a_n: 1, 2, 2^2, 2^{(2^2)}, 2^{(2^{(2^2)})}$? – AlkaKadri Jul 3 at 22:48

Let $$a_i = 2^{x_i}, x_i = p_1^{p_2^{\cdots ^{p_i}}}$$

Then $b_i = a_i - a_{i-1} = a_{i-1} \cdot (2^{(x_i - x_{i-1})} - 1)$

Remove the trivial factor as:

$$\frac{b_i}{a_{i-1}} = 2^{(x_i - x_{i-1})}-1$$

Also it's divisible by $3$ since difference between exponents is even.

  • How would I then factor $\frac{b_i}{a_{i-1}}$ ? You've mentioned that it is divisible by 3, but how would I figure out other divisors? – AAC Aug 29 at 18:18

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.